Myoepithelial Carcinoma of the Breast Treated with Surgery and Chemotherapy - Yumi Endo; Hiroshi Sugiura; Hiroko Yamashita; Satoru Takahashi; Nobuyasu Yoshimoto; Mai Iwasa; Tomoko Asano; Tatsuya Toyama (Case Reports in Oncological Medicine)
Myoepithelial carcinoma (malignant myoepithelioma) of the breast is a rare tumor, for which only a limited number of reports have been published. Most of the reports emphasized diagnosis and pathology but not biological behavior and treatment. We report a 61-year-old patient with breast myoepithelial carcinoma who developed locoregional and distant metastases and received many chemotherapy regimens. She presented with an elastic hard mass of the left breast. Breast conserving surgery was performed as part of both diagnosis and treatment. From the results of histological and immunohistochemical examinations, this case was considered to be a myoepithelial carcinoma. Fifteen months after the completion of adjuvant radiotherapy, distant metastasis of the left parasternal lymph node metastasis developed. She was treated by further excision and received a total of four regimens of chemotherapy including a combination of doxorubicin and cyclophosphamide. She received chemotherapy for 20 months after the diagnosis of metastasis.